Educação e diferença: uma experiência docente em artes visuais na comunidade surda - Huppes, Sara Beatriz Eckert (2018)
This research proposes to think a teaching experience in Visual Arts, in a bilingual school, with deaf students. It aimed to articulate education permeated by the concepts of difference, experience, territory and language, through authors such as Carlos Skliar (2014), Jorge Larrosa (2010), Gilles Deleuze and Félix Guattari (1997). Therefore, this is not a comparison in relation to other educational spaces, but it approaches possibilities of experience within the space in which one lives. It presents as research question: how could one write (with) a pulsating life within the teaching experience in Visual Arts with deaf students? The concepts were thought in the educational field through the reasoning of the philosophies of difference and the experiences lived at State School of Special Education Dr. Reinaldo Fernando Cóser, in Santa Maria - RS. Thus, as methodology, it operated with the biographematic writing as a possibility for producing research with the method developed by Roland Barthes (2003), which sees life as a text construction; consequently, the research does not aim at narrating a story script, but it presents life as potency. As results, memories were activated in relation to places lived during childhood, a diary was produced, and a photographical composition of images of the process was conceived. All these elements influenced the teaching experience and produced biographemes in this thesis.